Learning strategies for Islamic religious education in building student morals at Muhammadiyah 48 Middle School Medan - Sampurna Munthe (Institute of Accounting Research and Novation (IARN), 2023)
This research uses a type of qualitative research with a qualitative naturalistic approach, which is a type of research that examines data that describes complex and concrete social realities. In addition, this study uses data collection techniques by means of observation, interviews and documentation. Meanwhile, data analysis techniques were carried out through data reduction, data presentation, and conclusions drawn during data collection. The results of the research conducted at Muhammadiyah 48 Middle School in Medan showed that the learning strategy for PAI teachers was quite good because the learning strategies for PAI teachers varied during the teaching and learning process, therefore the learning strategies for PAI teachers were effective. modeling, habituation patterns and team building strategies and others. PAI teachers are role models that students should emulate. PAI teachers provide religious advice to students and set a noble example. The morals of students at SMP Muhammadiyah 48 Medan are quite good, this can be seen when students are at school, reflecting good behavior, respect for teachers and love for friends, and maintaining school cleanliness and discipline in coming to school. This PAI teacher learning strategy is quite good but needs to be improved again so that students are able to become good role models for families and society.